The Infusion of Propaganda in the Music Education in China - Louie Galvez Giray (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Under the administration of the Communist China, the distinction between education and propaganda cannot be made. Various research and literatures reveal that many resources used by Chinese educational institutions, such as books and songs, are modified in order to inject views that favor People’s Republic of China and ideologies from the Communist Party. This perspective paper explores the infusion of propaganda undertaken in the education in the Communist China. It also provides a discussion on both the advantages and disadvantages of such conduct. Particularly, it elaborates on the concepts of self-preserving maneuver for social stability and country’s survival; emphasis on the welfare of the state; the domino effect in altering musical pieces; corrupted education and altered truth; manifestation of the superiority and authoritarianism of the ruling party; and the ideological remolding to establish loyalty and nationalism. It is recommended that in order for China to be faithful to its slogan, diversity in unity, respecting differences on musical works of ethnicities and not intervening on them would be a decent starting point.